Childhood lichen planus pemphigoides triggered by chickenpox - T S Mohanarao; Gummalla Ajay Kumar; Kavya Chennamsetty; T Priyadarshini (Wolters Kluwer Medknow Publications, 2014)
Lichen planus pemphigoides (LPP) is a rare autoimmune bullous disorder that is rarer in children characterized by bullae on lichen planus like papules and the normal looking skin. Clinical, histopathological and direct immunoflourescence evaluation is important for the diagnosis of this entity. We report a case of LPP in a 5-year-old girl child probably triggered by an episode of preceding varicella. Diagnosis was confirmed by histopathology and immunofluorescence examination. Histological findings were typical of lichen planus from the biopsy taken from a violaceous to erythematous papule and characteristic of bullous pemphigoid in the biopsy taken from a bullous lesion with evidence of immunoglobulin G and C3 deposition along the basement membrane zone on direct immunofluorescence.